Social capital and empowerment among squatter settlers in Tehran, Iran - Babaei, Hamidreza (2012)
Squatter settlers live in situations of poverty with a lower cost of opportunity and less financial and human capital than wealthy people. These people usually live with expanded poverty, lack in basic living facilities and are exposed to various social deviations that together with the special cultural structure have made these communities crisis-generating regions. poverty is known as a multidimensional phenomenon, hence, poor people need empowering with a variety of resources and capabilities at the individual and collective level. Empowerment has become an essential tool for enabling marginalized people to expand their access to resources and enhance their own experiences. Empowerment is defined as the extension of assets and the capability of poor people to participate and negotiate with influence, control, and hold accountable institutions that affect their lives. Social capital has been acknowledged as an efficient means for poverty reduction among the poor. Social capital, involving bonding, bridging and linking, in its best form, contributes to economic, social,psychological and political development by providing information distribution,mitigating opportunistic behaviour, and facilitating communal decision-making and empowerment. This study sets out to examine the role of bonding, bridging and linking social capital for predicting the psychological and financial assets and empowerment among squatter settlers in Iran, Tehran. This study used the survey technique and questionnaires to collect the data from 328 selected respondents in two squatter settlement communities in Tehran (Islamabad and Bagh-e-Azari). The results reveal that bonding social capital has a higher level than other dimensions of social capital among squatter settlers in Tehran. The results indicated that social capital significantly predicts empowerment among squatter settlers. Concerning the social capital dimensions the results indicate that all three dimensions of bonding, bridging and linking social capital positively predict empowerment among squatter settlers. With regards to empowerment dimensions (psychological and financial), the results indicate that bonding social capital predicts financial assets while bonding, bridging and linking together predict psychological assets among squatter settlers. Education, employment status and gender significantly predict social capital, and education, income, marital status and household size significantly predict empowerment among squatter settlers. Taken together the findings of this study suggest that bonding, bridging, and linking social capital are linked to empowerment. The results suggest noteworthy implications for theory and practice. The findings of this study have improved our understanding of the factors predicting financial and psychological assets among squatter settlers in Iran. The overall results indicate that the theories of bonding, bridging and linking social capital have provided a good understanding of empowerment predictors and the majority of the findings appear to support the existing theories. Since the bridging and linking of social capital among squatter settlers was at a low level among community workers, social planners and social policymakers might focus on expanding and building, bridging and linking social capital to empower the squatter settlers.